The Analysis of the Brain Dominance and Language Learning Strategy Used by University EFL Learners - Suwarto Suwarto; Arini Hidayah (Journal of General Education and Humanities, 2023)
This study examined (1) the brain dominance pattern and language learning approaches, (2) the role of brain dominance toward each category of language learning strategies, (3) whether there was a significant difference, and (4) the effect. The participants in this study were 99 students in Universitas Veteran Bangun Nusantara by random sampling. Language Learning and Brain Dominance Questionnaires collected data. The brain dominance score and language learning strategies score were calculated and analyzed by analysis of variance to investigate any difference between brain dominance and learning strategies. The result: (1). The highest mean students’ language learning strategies use was cognitive strategies (2) Each language learning strategy category differed significantly between left, whole, and right-brained students. (3) Left-brain and whole-brain effects on student language learning strategies were the same. (4). Students' learning tactics vary by brain type.